De novo in vitro shoot morphogenesis from shoot tip-induced callus cultures of Gymnema sylvestre (Retz.) R.Br. ex Sm - Tasiu Isah (Biological Research, 2019)
Abstract Background Gymnema sylvestre is a medicinal woody perennial vine known for its sweetening properties and anti-diabetic therapeutic uses in the modern and traditional medicines. Its over-exploitation for the therapeutic uses and to meet the demand of pharmaceutical industry in raw materials supply for the production of anti-diabetic drugs has led to considerable decline in its natural population. Results An efficient system of shoot bud sprouting from nodal segment explants and indirect plant regeneration from apical meristem-induced callus cultures of G. sylvestre have been developed on Murashige and Skoog (MS) medium amended with concentrations of cytokinins. Of the three growth regulators tested, N 6-benzylaminopurine (BAP) was the most efficient and 2.0 mg L−1 gave the best shoot formation efficiency. This was followed by thidiazuron (TDZ) and kinetin (Kin) but, most of the TDZ-induced micro shoots showed stunted growth. Multiple shoot formation was observed on medium amended with BAP or TDZ at higher concentrations. The produced micro shoots were rooted on half strength MS medium amended with auxins and rooted plantlets acclimatized with 87% survival of the regenerates. Conclusions The developed regeneration system can be exploited for genetic transformation studies, particularly when aimed at producing its high yielding cell lines for the anti-diabetic phytochemicals. It also offers opportunities for exploring the expression of totipotency in the anti-diabetic perennial vine.